2007
DOI: 10.1038/sj.ijir.3901554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfuzosin 10 mg once daily on sexual function in men treated for symptomatic benign prostatic hyperplasia

Abstract: We evaluated the effects of extended-release alfuzosin HCl 10 mg once daily (q.d.) on sexual function in men with lower urinary tract symptoms associated with benign prostatic hyperplasia (BPH). In a randomized, double-blind, placebo-controlled study of men aged Z50 years, after a 28-day placebo run-in period, patients were randomized to receive alfuzosin 10 mg q.d. or matching placebo for 28 days. The mean change from baseline (day 1) in sexual function on day 29 was assessed using the Danish Prostate Symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…[7][8][9] Earlier reports concerning the clinical efficacy of alfuzosin in the treatment of symptomatic BPH and its concomitant effect on sexual function have suggested that the improvement in LUTSs is strongly associated with the improvement in sexual function. 10,11 Most of the earlier studies used changes in the Danish prostate symptom sex score (DAN-PSSsex) or the international index of erectile function (IIEF) questionnaire score as the parameter of improvement in sexual function. However, sexual function is complex and includes multiple domains, including sexual desire and erectile and ejaculatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Earlier reports concerning the clinical efficacy of alfuzosin in the treatment of symptomatic BPH and its concomitant effect on sexual function have suggested that the improvement in LUTSs is strongly associated with the improvement in sexual function. 10,11 Most of the earlier studies used changes in the Danish prostate symptom sex score (DAN-PSSsex) or the international index of erectile function (IIEF) questionnaire score as the parameter of improvement in sexual function. However, sexual function is complex and includes multiple domains, including sexual desire and erectile and ejaculatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Double-blind comparative studies also failed to show significant benefits of alfuzosin over other a 1 -adrenoceptor antagonists with regard to sexual function. 4 Although the study by Chung et al confirms that we do not have to expect worsening of sexual function when using this or other a 1 -adrenoceptor antagonists, 3 we feel that claims for efficacy in improving sexual function based upon open-label studies are inappropriate. The key reason for this is that overall sexual function may also exhibit considerable improvement upon placebo treatment in men with voiding dysfunction.…”
mentioning
confidence: 93%
“…[1][2][3] Furthermore, recent studies, not only in open label studies but also in randomized double-blind, placebo-controlled studies showed that Alfuzosin 10 mg once daily significantly improved LUTS and sexual function. [4][5][6] As you pointed out, we agree that efficacy in improving sexual function based upon doubleblind randomized comparative trial (RCT) are appropriate. Before considering the policy implications of our findings, some methodological aspects of the study need to be considered.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A 3-year follow up of European men treated with alfuzosin 10 mg once daily for LUTS suggestive of BPH in 'real-life practice' showed that ejaculatory disorders were uncommon (0.4%) [Vallancien et al 2008]. In a prospective study evaluating the effect of alfuzosin on sexual function in men with LUTS, after 1 month of treatment, men had no adverse effect on ejaculatory function [Rosen et al 2007]. On the other hand, alfuzosin treatment in men with LUTS was associated with improvement in ejaculatory function.…”
Section: Prevalence Of Non-pe Ejd In Patients With Other Medical Condmentioning
confidence: 99%